Culture and Music Psychology - Kok, Keegan Qi Xian (Curtin University, 2024)
Music is evidently a product of culture. As such, it is reasonable to think that culture influences music consumption, but little research within the field of music psychology concerns cultural variables. The current thesis investigated culture’s influence on music consumption through two domains, namely musical taste and uses of music. Findings support the overall research question where culture indeed shows an influence on music consumption at the individual and country-level.